Relationship between Predisposing Factors and the Incidence of Contraceptive Dropout in West Java - Muaebah, Shiva; Susanti, Ari Indra; Didah, Didah; Gumilang, Lani; Martini, Neneng; Rosmawati, Dean (Global Medical & Health Communication (GMHC), 2023)
The incidence of contraceptive dropout in West Java is still high. Analyzing the reasons would help to improve programs. This study explores the relationship between predisposing factors and the incidence of contraceptive dropout in West Java. The research was cross-sectional and conducted from August to December 2021, and the dataset came from Program Performance and Accountability Survey (Survei Kinerja dan Akuntabilitas Program, SKAP) 2019. The sample in the study were women of childbearing age 15–49 years with married status both ever and currently using contraception—a total of 338 samples with simple random sampling. This study used univariate, bivariate, and multiple logistic regression to analyze the discontinuation of contraception. A study has shown a relationship (p<0.05) between parity, education level, level of knowledge, and the incidence of contraceptive dropout. Furthermore, age and employment status did not affect them. In conclusion, a relationship exists between predisposing factors such as education, parity, knowledge, and contraceptive dropout. There is a need to emphasize the health promotion of contraception, especially for women of childbearing age with marital status, low education, fewer children than two, and inadequate knowledge level. In addition, contraceptive service standards should be implemented to prevent the incidence of contraceptive dropout.